Management of Renal Cell Carcinoma in Von Hippel-Lindau Syndrome: Case Report and Review of Literature - Aroona S.,; Shamsuddin O., (Department of Surgery, UKM Medical Centre, 2015)
Renal cell carcinoma (RCC) is the one of the most common type of of cancer of the kidneys affecting adults. A 35- year-old man, with Von Hippel Lindau (VHL) syndrome was referred for bilateral renal mass in a follow up CT for evaluation. Open partial left nephrectomy was performed and the final histopathological report confirmed the diagnosis. One of the most important genetic and hereditary risk factor for RCC is Von Hippel-Lindau syndrome (VHL). RCC in VHL may occur bilaterally in some cases, so preserving renal parenchymal function is a major therapeutic goal and nephron sparing surgery provides a favorable patient outcome.